Educational Tourism in Protected Natural Areas in South-East of the Baikal Region - Chizhova, Vera; Kirillov, Sergey; Slipenchuk, Mikchail (Quaestiones Geographicae, 2016)
The paper presents the implementation of the strategy of development of tourism in the south-east of the Baikal region on the territory of the Baikal Biosphere reserve and its subordinate federal sanctuaries. as a result of the field research conducted in the summer of 2014 by a group of staff and students of the Faculty of Geography, Lomonosov Moscow State university, a project of a tour route for the development of ecotourism and environmental education in the territory of Altacheysky sanctuary has been proposed.